COMPARISON OF SALIVARY pH BEFORE AND AFTER CONSUMING A SOLUTION OF SUGAR AND PALM SUGAR IN DENTISTRY FACULTY’S STUDENT OF ANDALAS UNIVERSITY - Risa Widia; Nila Kasuma (Faculty of Dentistry Universitas Andalas, 2018)
Sugar ( sucrose ) is a carbohydrate compound which is soluble in water and directly absorbed by the body to convert into energy . Diet sugar ( sucrose ) can affect the pH of saliva , where the compounds have fermented in the mouth which produces acid to lower the pH of saliva and the results of this activity will initiate the process of demineralization of tooth structure. The palm sugar contains sucrose higher at 84 % compared with 20 % of sugar cane.8 The purpose of this study was to determine differences in comparison the pH of saliva before and after consuming a solution of sugar and palm sugar. This study was an experimental study using pre-test and post-test design. The samples used as many as 26 people. Each sample was given treatment consumes sugar and palm sugar solution. Salivary pH measurements using dental saliva pH indicator. Analysis of data using the Wilcoxon test. The result show an average difference in the pH of saliva after consuming a solution of sugar of 0.57 ± 0.32 while the average difference in the pH of saliva after consuming palm sugar solution at 0.67 ± 0.40. The value of p> 0.05 so there is no significant difference. Based on the research that has been done, it can be concluded that consuming a solution of sugar and palm sugar solutions together can decrease the pH of saliva. Keywords : salivary pH , sugar solution , palm sugar solution